Introduction of a Novel Smartphone-Coupled Blood Glucose Monitoring System. (November 2017) - Jendrike, Nina; Baumstark, Annette; Chen, Chieh-Hsiao; Rittmeyer, Delia; Haug, Cornelia; Freckmann, Guido
The novel system for self-monitoring of blood glucose (SMBG) PixoTest couples SMBG to a smartphone and does not require a separate glucose meter. The integrated system includes all components necessary for a glucose measurement, and owing to a colorimetric measurement principle, a smartphone camera can capture color changes and a software app calculates the corresponding glucose value. In the presented study, the system was evaluated in terms of system accuracy as described in ISO 15197:2013. It was shown to fulfill system accuracy requirements with 97-99% of results from three different reagent system lots within the accuracy limits and 100% of results within zone A of the consensus error grid.